PENGARUH PERILAKU IBU TENTANG ANTENATAL CARE TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PARGARUTAN KECAMATAN ANGKOLA TIMUR KABUPATEN TAPANULI SELATAN TAHUN 2026 - Fitria Lely Effina Batubara; Ummi Irmadani Harahap; Efrida Yanti; Miftahuljannah Miftahuljannah (Ensiklopedia of Journal, 2026)
Anemia is a health problem experienced by women worldwide, especially in developing countries. The World Health Organization (WHO) reports that the prevalence of anemia in pregnant women is around 35-75%, and this number increases with increasing gestational age. According to the WHO, 40% of maternal deaths in developing countries are related to anemia. Minister of Health Regulation number 97 of 2014 mandates that maternal health services during pregnancy be carried out through comprehensive and quality antenatal care (ANC) services, in order to prepare for a clean, safe, and healthy delivery during pregnancy. This study aims to determine the effect of maternal behavior regarding antenatal care on the incidence of anemia in pregnant women at the Pargarutan Community Health Center, East Angkola District, South Tapanuli Regency. This type of research is an observational analytical study with a cross-sectional approach. The sampling technique in this study was carried out by consecutive sampling, where all subjects who came sequentially were included in the study until the number of subjects was met with a total of 90 pregnant women. The results of this study indicate that there is an influence of knowledge (p = 0.035) on the incidence of anemia in pregnant women, there is an influence of attitude (p = 0.025) on the incidence of anemia in pregnant women, there is an influence of action (p = 0.003) on the incidence of anemia in pregnant women, and the most dominant variable influencing the incidence of anemia in pregnant women is the action variable (p = 0.001; OR = 6.879).Keywords: Behavior, Antenatal Care, Anemia in Pregnant women